2021
DOI: 10.1111/1745-9125.12299
|View full text |Cite
|
Sign up to set email alerts
|

In the shadow of 9/11: How the study of political extremism has reshaped criminology*

Abstract: for their helpful comments on earlier drafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…Criminology has however been credited with bringing its data collection procedures, analytic approaches, and empirically tested theories that have been developed over the past 250 years to understanding terrorism (Agnew 2010;Haner and Sloan 2021;LaFree and Dugan 2015;LaFree 2021). Stemming from Beccaria's (1764a) seminal work for example, criminological studies have demonstrated that while counterterrorism strategies aimed at deterring terrorism may work under certain conditions (Carson 2014;2017;LaFree, Dugan, and Korte 2009), strategies aimed at deterrence can also incite terrorist backlash increasing the number of attacks and fatalities (Argomaniz and Vidal-Diez 2015;Dugan and Chenoweth 2012;Fisher and Becker 2021;Hsu, Vasquez, and McDowall 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Criminology has however been credited with bringing its data collection procedures, analytic approaches, and empirically tested theories that have been developed over the past 250 years to understanding terrorism (Agnew 2010;Haner and Sloan 2021;LaFree and Dugan 2015;LaFree 2021). Stemming from Beccaria's (1764a) seminal work for example, criminological studies have demonstrated that while counterterrorism strategies aimed at deterring terrorism may work under certain conditions (Carson 2014;2017;LaFree, Dugan, and Korte 2009), strategies aimed at deterrence can also incite terrorist backlash increasing the number of attacks and fatalities (Argomaniz and Vidal-Diez 2015;Dugan and Chenoweth 2012;Fisher and Becker 2021;Hsu, Vasquez, and McDowall 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Political science (Asal, Naga, and Rethemeyer 2014; Chenoweth 2013; Crenshaw 2000; Hoffman 2002), psychology (Kruglanski and Fishman 2006; Moskalenko and McCauley 2011; Victoroff 2005), economics (Benmelech, Berrebi, and Klor 2012; Blomberg, Hess, and Weerapana 2004; Sandler and Enders 2004), and more recently peace (Jackson 2000; Lopez 1995; Toros 2015) and security studies (Benson 2014; Dixit 2014; O’Rourke 2009), among others, also provide valuable insights to understand terrorism and responses to it. Criminology has however been credited with bringing its data collection procedures, analytic approaches, and empirically tested theories that have been developed over the past 250 years to understanding terrorism (Agnew 2010; Fisher and Dugan 2019; Haner and Sloan 2021; LaFree and Dugan 2015; LaFree 2021). Stemming from Beccaria’s (1764a) seminal work for example, criminological studies have demonstrated that while counterterrorism strategies aimed at deterring terrorism may work under certain conditions (Carson 2014, 2017; LaFree, Dugan, and Korte 2009), strategies aimed at deterrence can also incite terrorist backlash increasing the number of attacks and fatalities (Argomaniz and Vidal-Diez 2015; Dugan and Chenoweth 2012; Fisher and Becker 2021; Hsu, Vasquez, and McDowall 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These insights have also borne benefits to the field of criminology as well. Similar to white-collar crime research's influence on the field in the twentieth century, terrorism research over the last two decades has enabled many of the assumptions about criminality more broadly to be examined (LaFree 2021). For example, criminologists studying terrorism have questioned broader links to socio-economic status, self-perceptions of criminality, and how generalizable findings are internationally (LaFree 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations